Some local Forms of Known Convergences of Sequence of Real Valued Functions (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
Using the notions of local uniform and strong local uniform con-vergence for the sequence of real valued functions or with value in metric space, the class of locally equally and strong locally equally convergences are studied. We are concern to dependence of type of some convergences from the neighborhood of the limit point. The known locally uniformly convergence is a key of some applications of this idea. We can reformulate one type of Arzela Theorem and nd relations of this convergence with quasi-uniformly by segments of Alexandro off convergence. Beside this type of convergence, we focus to another convergence which is nearer the well known a-convergence.